Prepared for the Worst . . . and the Best: The Mannlicher Carcano Radio Hour Continues Keeping People Together During COVID-19 - Kent, Brendan (Critical Studies in Improvisation / Études critiques en improvisation, 2021)
When physical distancing became necessary as a result of COVID-19, I wanted to find out how to make music in real time over the internet. Fortunately, I found the Mannlicher Carcano Radio Hour! This improvisational collective has a history of networked performance—now facilitated via the conferencing platform Zoom—that stretches back to its origins in experimental call-in radio collage during the 1990s. This ‘community voices’ piece describes some of the ways participants from around the world join together on Saturdays to improvise and socialize as a networked community.